2012
DOI: 10.3390/ijms13021658
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of TiO2 Nanocrystallite Powders Coated with 9 mol% ZnO for Cosmetic Applications in Sunscreens

Abstract: The preparation of TiO2 nanocrystallite powders coated with and without 9 mol% ZnO has been studied for cosmetic applications in sunscreens by a co-precipitation process using TiCl4 and Zn(NO3)2·6H2O as starting materials. XRD results show that the phases of anatase TiO2 and rutile TiO2 coexist for precursor powders without added ZnO (T-0Z) and calcined at 523 to 973 K for 2 h. When the T-0Z precursor powders are calcined at 1273 K for 2 h, only the rutile TiO2 appears. In addition, when the TiO2 precursor pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Additionally, the free radical production was observed to be inhibited and was attributed to a free radical scavenging effect. Commonly used coating materials include wide Eg metal oxides, such as silica (SiO 2 ) [13] and alumina (Al 2 O 3 ) [14] however, conflicting reports have shown that such composites could in fact enhance the photoactivity [15], thus alternative materials such as polymers have also been investigated [16]. One promising coating/encapsulating material is the natural polymer chitosan.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the free radical production was observed to be inhibited and was attributed to a free radical scavenging effect. Commonly used coating materials include wide Eg metal oxides, such as silica (SiO 2 ) [13] and alumina (Al 2 O 3 ) [14] however, conflicting reports have shown that such composites could in fact enhance the photoactivity [15], thus alternative materials such as polymers have also been investigated [16]. One promising coating/encapsulating material is the natural polymer chitosan.…”
Section: Introductionmentioning
confidence: 99%
“…From 600 to 650°C there is a notable decrease in catalytic activity, which cannot be ascribed to any marked change in specific surface area (Figure 3), anatase crystal size or apparent rutile content ( Figure 5). However, it is well known that the onset of the transformation from anatase to rutile occurs at around 600°C [11] in a nucleation process at anatase (112) twin boundaries [39], and therefore the rutile nuclei that are formed around the anatase crystals might alter their photocatalytic properties before the amount of the rutile phase surpases the detection limit of the X-Ray diffractometer. It is for this reason that the decrease in catalytic activity from 600 to 650°C is ascribed to the onset of rutile formation, as indicated in Figure 8 shows the decay of the methylene blue concentration corresponding to the three catalysts.…”
Section: [Figure 7]mentioning
confidence: 99%
“…Therefore developing a method of obtaining cheap, pure ZnO with small, controlled size is highly desirable. Common synthesis methods include co-precipitation from zinc salts solution with an alkali such as sodium hydroxide, force hydrolysis, sol-gel or pyrosol [15][16][17][18]. Out of these methods, co-precipitation method is very facile and convenient method.…”
Section: Introductionmentioning
confidence: 99%